Research and Prospect of Defense for Integrated Energy Cyber–Physical Systems Against Deliberate Attacks - Tianlei Zang; Xiaoning Tong; Chuangzhi Li; Yahui Gong; Rui Su; Buxiang Zhou (Energies)
The tight integration of cyber and physical networks in integrated energy cyber–physical systems (IECPS) improves system awareness and coordinated control but also heightens susceptibility to targeted attacks. A robust IECPS defense system is crucial for increasing the system’s resilience against deliberate attacks. Reducing the associated risks is essential to ensure the safe and stable operation of IECPS. In order to enhance the defense capability of IECPS against deliberate attacks, this paper discusses cyberattacks, physical attacks, and coordinated cyber physical attacks (CCPAs) in detail. The attack principles and attack models of each type of attack are described, and then the intentional attack threats faced by IECPS are analyzed. Based on this, the paper reviews the current research landscape regarding countermeasures against deliberate attacks, categorizing the findings into three key areas: preemptive prevention, process response, and post–event recovery and summarizing. The theoretical foundations, system planning, optimal scheduling, and cyber security technologies required for existing defense research are further elaborated. The unresolved issues within these key technologies are analyzed and summarized, followed by the presentation of the problems and challenges faced in defending against deliberate IECPS attacks.